Strategi Peningkatan Literasi Keuangan Syariah di Masyarakat: Peran Pendidikan dan Kampanye - Maghfira Izzany (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The low level of Islamic financial literacy in Indonesia is a serious challenge in realizing a financial system that is inclusive and in accordance with Islamic values. Islamic financial literacy reflects an individual's understanding of financial concepts and products based on sharia principles such as the prohibition of riba, gharar, and maysir, as well as the importance of fairness and social responsibility. This article aims to evaluate strategies to improve Islamic financial literacy by emphasizing on two main approaches: education and public campaigns. The method used is a literature study by reviewing various academic literatures, financial institution reports, as well as practices in other countries that have successfully implemented Islamic financial literacy widely. The results of the study show that formal education such as the integration of Islamic finance materials in the school curriculum, as well as non-formal education in the form of training and counseling, contribute significantly to improving public understanding. On the other hand, public campaigns through social media, educational videos, and collaboration with religious leaders have proven effective in reaching various segments of society, especially the younger generation. This study concludes that improving Islamic financial literacy requires a holistic and synergistic approach between education, campaigns, and regulatory support from the government and financial institutions. Recommendations include thematic curriculum development, training for educators, and sustained digital-based campaigns. The findings of this article are expected to make practical and theoretical contributions to the development of Islamic financial literacy strategies in Indonesia.